Analysis of flexible silver-printed NFC tag antenna on miniaturization and bending effect / Najwa Mohd Faudzi ... [et al.] - Mohd Faudzi, Najwa; Razali, Ahmad Rashidy; Abdul Manaf, Asrulnizam; Abd Rahman, Nurul Huda; Aziz, Ahmad Azlan; Ibrahim, Amiruddin; Mozi, Aiza Mahyuni (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
Size and flexibility are the two main elements that must be considered in designing a near-field communication (NFC) tag antenna because they will determine the performance of the whole system. The previously designed NFC tag antenna, which is made of a rigid substrate such as FR-4, limited the application of the tag to only on a flat surface. The size of the tag antenna also needs to be optimised based on the application requirements since different sizes of the antenna will contribute to different electrical properties, including inductance and resistance. Therefore, this paper presents an analysis of a flexible printed tag antenna with different miniaturisation sizes and bending effects for NFC systems. The operating frequency of the proposed NFC tag antenna is 13.56 MHz, which is the same frequency as the NFC reader, allowing them to be coupled and to communicate with each other. Three sizes of silver printed tag antenna are presented, and the performance of the tag during bending is analyzed. Other tag antenna parameters and characteristics, including reflection coefficient, inductance, resistance, read range and output voltage, are also observed through simulation and accordingly measured. The results show that the Design 1 antenna has demonstrated the highest measured tag reading range of 3 cm, while the Design 2 antenna has shown good flexibility, withstanding bending at various angles and exhibiting a minimum reading range of 0.5 cm. Overall, the correlation between antenna size, flexibility and antenna performance has been determined and systematically validated.